The Brain and Causality: How the Brain Becomes an Individual-Level Cause of Illness. (8th September 2020) - Halpin, Michael
Abstract: How do individual-level explanations become applied to social issues? Neurobiology – the study of the connections between behavior and the cells and structures of the brain – receives substantial public funding and influences social institutions, policy debates, and core aspects of human experience. With respect to mental health, neurobiology has ramifications for the way disorders are defined, diagnosed, and treated, along with how public funding for mental illness is allocated. This article addresses how neurobiologists establish the brain as a cause of mental illness. I analyze 17 months of ethnographic observation at a well-regarded neurobiological research laboratory, as well as observations at professional meetings, to detail three strategies: Linking the Brain to Mental Illness, Explaining Mental Illness with the Brain, and Asserting the Causal Importance of the Brain . These strategies first connect the brain to mental illness, and subsequently establish the causal primacy of the brain relative to alternative explanations (e.g., poverty). I connect findings to medical sociological theories, biological reduction, and emerging national health policies.